JAZODAN MUDDATIDAN ILGARI SHARTLI OZOD QILISH: TUSHUNCHASI, TARTIBI VA SHARTLARI - Rustamov Xumoyun Akbarjanovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the essence of the institution of conditional release from prison, its legal basis, the procedure for its application based on the Criminal Code of the Republic of Uzbekistan and other regulatory documents, and the role of the probation department in this process. It also covers the social significance of conditional release, the processes of adaptation of convicts to society and resocialization.